Strength through sharing: Mi'kmaq political thought to 1761 - Leech, David J (University of Ottawa (Canada), 2006)
We stand witness at the dawn of the 21st century to increasing tensions between Aboriginal people in Canada, and the Canadian state, largely as a result of conflict over natural resources. Do these conflicts imply that we are unable to understand each other? Does the meaning of our words get 'lost in translation' as it crosses the space between us? If this is so, then how can we envision dialogue between the two craft depicted in the Kaswentha, when---from a Canadian perspective---we don't understand the words each of us is using? When we don't understand the meaning of 'sovereignty' from the perspective of an Aboriginal participant in the dialogue, how can we understand what possibilities of cooperation are open to us? The Mi'kmaq, in their own traditions and 'worldview', clearly articulated their own understanding of 'sovereignty' based on their traditions of political thought and action. Through their economic, legal, spiritual, political and 'environmental' articulations, the Mi'kmaq projected their understanding of 'sovereignty' into the creation of relationships with the French, Jesuit and English immigrants which arrived on their shores. Through an analysis of these articulations, we gain a new appreciation for Mi'kmaq sovereignty---one founded on the concept of sharing. The three pillars of continuity, responsibility---for themselves and their 'extended European kin'---and relationship-building characterized this shared space within which the Mi'kmaq founded their relationship with their blue-eyed 'kin'. In all of its aspects---environment and land; spiritual, political and legal; and economic---Mi'kmaq sovereignty was about the paths and passes that allowed them to build relationships with others. Indeed, in its content and structure, Mi'kmaq sovereignty was, and is, shared sovereignty---an idea that opens our minds to a new way of understanding the political landscape of 21st century Mi'kma'ki. Drawing on this concept of shared sovereignty, ideas with respect to the co-management of natural resources are discussed. These ideas draw to a conclusion the thesis, and open avenues for further research and reflection on the place of Aboriginal political thought in the foundations of political culture in Canada.
Keywords: Political Science, General.; Native American Studies.